2017
DOI: 10.1002/ece3.3632
|View full text |Cite
|
Sign up to set email alerts
|

Habitat heterogeneity affects predation of European pine sawfly cocoons

Abstract: Habitat heterogeneity is thought to affect top‐down control of herbivorous insects and contribute to population stability by providing a more attractive microhabitat for natural enemies, potentially leading to reduced population fluctuations. Identifying the parameters that contribute to habitat heterogeneity promoting top‐down control of herbivorous insects by natural enemies could facilitate appropriate management decisions, resulting in a decreased risk of pest insect outbreaks because of a higher level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
0
10
2
Order By: Relevance
“…Throughout the life cycle of N. sertifer, mortality caused by parasitoids in the egg and larval stages, walking predators like spiders and ants in the early larval stages, and small mammals in the cocoon stage are found to be important predators. The predation rates of N. sertifer cocoons imposed by small mammals are known to be positively affected by forest structure (Hanski and Parviainen 1985;Kollberg et al 2014;Bellone et al 2017). Here we found that parasitoids seemed to be affected by tree size but not tree diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the life cycle of N. sertifer, mortality caused by parasitoids in the egg and larval stages, walking predators like spiders and ants in the early larval stages, and small mammals in the cocoon stage are found to be important predators. The predation rates of N. sertifer cocoons imposed by small mammals are known to be positively affected by forest structure (Hanski and Parviainen 1985;Kollberg et al 2014;Bellone et al 2017). Here we found that parasitoids seemed to be affected by tree size but not tree diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence comes from mixing conifers with broadleaved trees [33], where mixtures had higher parasitoid abundance [115] and overall predator richness [84••]. For the pine sawfly (Neodiprion sertifer) in Scandinavia, mortality rates were higher in mixed stands than in pine monocultures [116], which was mediated top-down by ant abundances ( [117], see also [9]). In the same observational system, parasitism rates of sawfly larvae increased with host tree size [11], suggesting size-dependent identity effects.…”
Section: Identity Effectsmentioning
confidence: 99%
“…Besides acting as breeding substrate for many forest species [ 2 ] it is an important structural component, providing for shelter and altering micro-climate [ 3 ]. Dead wood may also affect top-down regulation of herbivores through effects on their natural enemies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, forest heterogeneity and complexity created by dead wood could alter ecological processes such as pest suppression [ 4 ]. Higher predation rates of European pine sawfly cocoons were found when dead wood was present in monocultures [ 4 ], potentially by providing shelter to small mammalian predators [ 17 ].…”
Section: Introductionmentioning
confidence: 99%